Characterizing early initiation of illicit drug use by generation: A retrospective study - Dina Nashed; Cara Stokes; Sara Warfield Kelly (Emerging Trends in Drugs, Addictions, and Health)
Objective: This study identified factors associated with early initiation of substance use. Method: This study uses cross-sectional pooled data from the 2015–2019 National Surveys on Drug Use and Health (NSDUH), which is a nationally representative sample of adolescents and adults assessing substance use and mental health. We sought to identify factors associated with early initiation of substance use. Results: Among the study sample, 27.9 % initiated drug use prior to 18 years of age. Multivariable logistic regression models revealed that the odds of early initiation were greater among males (adjusted odds ratio [aOR] 1.42, 95 % Confidence Interval [CI]: 1.35–1.48), younger in age (aOR for 18–25 years old: 2.32, 95 % CI 2.14–2.49), and Non-Hispanic White (aOR 2.15, 95 % CI: 1.92–2.41). Additionally, it was found that the odds of early initiation were lower among those who resided in non-metro areas (aOR 0.88, 95 % CI: 0.82–0.95). Conclusions: Our study suggests that early initiation of drug use varies by demographic factors, and it continues to occur at earlier ages. Different prevention strategies should be tailored to address upstream factors that are associated with risky behavior among children and adolescents. Moreover, clinical strategies should further target younger age and should integrate mental health interventions as needed for those who were early initiators.